Climate Smart Village Report: Htee Pu Village, Myanmar - Thant, Phyu Sin; Myae, Chan; Barbon, Wilson John; Moe, May Zin; Hein, Pyae Phyo; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Htee Pu village in the Dry Zone was designated as Climate-Smart Village, where participatory action research was undertaken from 2018 to 2020 to find solutions to climate change's challenges to local farmers' lives and livelihoods. A Dry Zone is typically characterized by a lack of water, thin vegetation cover, and severe soil erosion. Nyaung U Township has the highest temperature in Myanmar's dry zone regions. With support from the International Development Research Centre (IDRC), Canada, the research project was implemented in Myanmar from July 2020 to July 2022. Htee Pu village was also one of the research areas in Myanmar to investigate the potential contributions of CSVs and CSA in enriching local food systems for better nutrition, enhancing livelihoods, increasing household resilience, and enhancing gender equity and inclusion. This brief aims to describe the updated profile of Htee Pu CSV in the Dry Zone, Myanmar, from 2018 to 2022.